Exploring the response of a resistive soot sensor to AC electric excitation. (August 2020) - Middelburg, L.M.; Ghaderi, M.; Bilby, D.; Visser, J.H.; Wolffenbuttel, R.F.
Abstract: The resistive particulate matter sensor is a simple device that transduces the presence of soot through impedance change across inter-digital electrodes (IDEs). We investigate the information provided by impedance spectroscopy over the frequency range from 100 Hz to 10 kHz for two purposes. The first is to investigate the opportunities for an improved sensor response to particulate matter (PM), based on the additional information provided by the measurement of both the in-phase (resistive) and out-of-phase (capacitive) components of the change in impedance over this frequency range as compared to DC resistance measurement only. Secondly, the origin of the capacitive response of the device is investigated from the perspective that soot on the device is in the form of bendable dendrites that grow in three dimensions. An IDE structure with the housing acting as an additional suspended electrode for introducing a controllable vertical electric field component has been used for this purpose. The formation of dipoles, due to bending of the charged dendrites, is found to be the source of the capacitive response. Simulation of electrostatic soot deposition reinforces dendritic self-assembly mechanisms, driven by charged particle trajectories along electric field lines. Optical microscopy confirms that dendrites growing out of the substrate plane are sensitive to electric and flow forces, bending when force balances are appropriate. We also apply impedance spectroscopy under varying electric field strengths, showing that capacitive response is only observed when conditions are conducive to dendrite bending in response to the applied AC electric fields. Highlights: Impedance spectroscopy in the 100 Hz to 10 kHz frequency range is applied to an IDE. The change in capacitance of the IDE is more gradual with PM deposit as resistance. A model for soot dendrite growth is validated by spectral permittivity measurement. Electrophoresis results in preferred soot deposition at IDE surface irregularities. A vertical electric field component results in vertical growth of soot dendrites.